İhaleye fesat karıştırma suçu - Arıtürk, Ramazan (My University, 2011)
hale, Fesat, Karıştırma, Açıklık, Eşitlik Rekabet ÖZET İHALEYE FESAT KARIŞTIRMA SUÇU Kamu ihale mevzuatımızda geçtiğimiz yıllarda köklü değişiklikler yapılmıştır. Bu kapsamda, 4734 Sayılı Kamu İhale Kanunu ve 4735 Sayılı Kamu İhale Sözleşmeleri Kanunu, daha sonra ise ihale düzenine aykırılıkların cezalandırıldığı, 765 sayılı Türk Ceza Kanunu’nu değiştiren 5237 sayılı Türk Ceza durumun bir yönü, ceza hukukuyla ilgili kısmı ele alınmıştır. İhaleye fesat karıştırma suçu, 765 Sayılı Türk Ceza Kanununda, farklı maddelerde dağınık ve unsurları da belirsiz bir şekilde düzenlenmişti. Bu durum konunun anlaşılmasını zorlaştırmakta, uygulamada sorunlara yol açmakta ve uygulama birliğini de zorlaştırmaktaydı. 5237 sayılı Türk Ceza Kanunu’nda uygulamada yaşanan bu sıkıntılar göz önünde bulundurulmak suretiyle ihaleye fesat karıştırma suçunun unsurları belirli hale getirilmiş, en önemlisi de suçun hangi hareketlerle işlenebileceği bizzat tayin edilmiştir. Çalışma her ne kadar doğrudan ihaleye fesat karıştırma suçunu konu ediniyor ise de, suçun unsurları konusunda yapılacak değerlendirme ihale mevzuatıyla yakından bağlantılı olduğundan zorunlu olarak ihale sistemi üzerinde durulmuştur. Bu kapsamda çalışma üç bölümden oluşmuştur. Buna göre; birinci bölümde, ihale kavramına ilişkin açıklamalara yer verilmiştir. İncelediğimiz suçun konusu, kamu kurum veya kuruluşları adına yapılan ihale olduğu için, birinci bölümün kapsamı bununla sınırlı tutulmuştur. Bu kapsamda birinci bölümde ihale usulleri üzerinde durulmuş, doğrudan temin ve tasarım yarışmalarının ihale usulü olup olmadığını değerlendirilmiştir. İhalede temel amaç, en uygun sözleşmecinin bulunup, idare açısından en elverişli sözleşmenin akdedilmesi olması nedeniyle, bu amacın sağlıklı bir şekilde gerçekleştirilmesine yönelik ilkelerin de bilinmesi ve ihale sürecini bu ilkelerin yönlendirmesi gerekmektedir. Bu önemi nedeniyle, çalışmanın bu bölümünde ihale mevzuatında yer alan ve ihale sürecine hakim olan bu ilkeler üzerinde durulmuştur. Çalışmanın ikinci bölümünde; ihale sürecine ilişkin açıklamalarda bulunulmuştur. İdarenin ihtiyacının ortaya çıkması ile ihale yapılmasına karar verilmektedir. Bu aşamada öncelikle ihalenin türü ve usulü belirlenip, daha sonra ihale sürecine başlanmaktadır. Belli bir prosedür izlenerek bu süreç tamamlanmakta ve bu süreçte ortaya çıkan ihlaller ise duruma göre ihaleye fesat karıştırmayı oluşturmaktadır. Çalışmanın üçüncü bölümde; münhasıran ihaleye fesat karıştırma suçu ele alınmıştır. Bu bölümde konu, tarihi gelişimden başlayarak incelenmiş ve Türk hukukundaki durum ele alınmıştır. Yine bu bölümde ihaleye fesat karıştırma suçu benzerlik arz ettiği suçlarla karşılaştırılmış, o suçlardan ayrıldığı yönlere yer verilmiştir. Hukukumuzdaki düzenlemenin yerindeliğinin değerlendirilmesi bakımından önem arz ettiğinden, mukayeseli hukuktaki düzenlemelere de yer verilmiştir. İhaleye fesat karıştırma suçuyla korunan hukuki değer, suçun unsurları, kusurluluğa ilişkin açıklamalar, suçun özel görünüş şekillerine ilişkin değerlendirmeler de bu bölümde ele alınan konuları oluşturmaktadır. Sonuç bölümünde ise ondokuz madde ile varılan sonuçlar tek tek ele alınarak yapılan çalışmanın bir kritiği, özeti ve varılan sonuç ele alınmıştır. Tender, Fraud, Transparency, Equality, Competitition

CRIMES ABOUT PUBLIC PROCUREMENT OF TURKISH CRIMINAL CODE In the recent years, radical changes were made within the Legislation of the Turkish Public Procurement. In this context, the Public Procurement Code (Law No. 4734) and Public Procurement Contracts Law (Law No. 4735) have later on punishes the violations of the procurements scheme and the Turkish Penal Code (Law No. 5237) which has amended old Turkish Penal Code (Law No. 765), in some ways discusses the relevant parts of the criminal law. The crime about Public Procurement, has previously distributed in different articles of the old Turkish Penal Code (Law No. 765) and the elements of this crime were not clearly specified. This situation, complicates the understanding of the issue, leads to problems in practice and makes the practical unity difficult. Hence the new Turkish Penal Code (Law No. 5237) have taken into consideration of such difficulties of the practice and have specified the elements of crime about the Public Procurement, more importantly, have determined under which acts does this crime is being committed. Notwithstanding, this study is directly involved with the crime about the public procurement law; since it is closely related with the legislation of the procurement law, it is necessarily focused on the procurement system. In this context, this study consists of three chapters. Accordingly, the chapter one contains descriptions in relation to the concept of the tender. Chapter one only involves the tender that is concentrated on the public institutions and organizations, since that is the subject of the crime that we are analyzing. Chapter one, in this regard, has emphasized on procedure of the tender and has examined as to whether the direct supply and the design competitions are recognized within the tender procedure. Due to the fact that the main goal of the tender is to find the best suitable contracting party and thus to establish the most appropriate contract that is in favor of the administration; accordingly in order to complete this goal in a healthy manner the related principles must be known and the progress of the tender must be oriented to this principles. As a consequence of its importance, these principles that exist under the procurement law and that are dominated by the tender process, have been emphasized on within this part of the work. Accordingly, the second chapter of this study describes the process of the tender. The tender is decided, once the need of the administration emerges. At this stage, initially the kind of the tender and its procedure are determined subsequently the tender process begins. A specific process is pursued and finalized; and the violations that have emerged during this process generate the crime about public procurement, on case-by-case basis. Chapter three of this study deals with the exclusivity of the crimes about the Public Procurement. The subject is examined within this chapter, starting from its historical developments, and the situation in Turkish Law is discussed. Once again, within this chapter, the crime about the public procurement is compared with other similar crimes; the parts that differentiate it from other crimes are also mentioned. The fact that our law gives great importance to the evaluation of the propriety, the regulations under the comparative law are also discussed. The protected legal value under the crime of the public procurement, its elements, explanations on the culpability, the assessments in relation to the special appearance of the forms of the crime are among some topics that are discussed within this chapter. A critique of a diligent work that is reached through the results of the nineteen articles, its summary and its conclusion remarks are discussed within this conclusion section.
Keywords: İhale_Hukuk; Kamu Hukuku